The Establishment and Spread of Acupuncture Model Based on Different Cultures - Yu Zhang; Sheng Liu (Wolters Kluwer Health/LWW, 2019)
The Belt and Road (B and R) brings a historic opportunity for the Chinese medicine culture communication, especially the traditional acupuncture. The high rate of acupuncture cognitive barriers is one of the important factors among patients and service providers in "B and R" countries. The proposed project, to be conducted in "B and R" countries, has the following primary aims: (1) to assess acupuncture knowledge, attitudes, and perceptions; (2) to assess acupuncture knowledge, attitudes, and perceptions among clinic staff; and (3) to adapt, develop, and deliver acupuncture education programs for patients and clinic staff. The secondary aims are as follows: (4) to explore the barriers that impact acupuncture receiving intervention and medical service and (5) to explore ways to help service providers to provide acupuncture services to patients in acupuncture clinics based on different cultures. Through an iterative process of discussion and revision, we plan to develop a comprehensive acupuncture intervention program that is appropriate for the "B and R" countries setting and that can be tested for its effectiveness in a series of controlled trials in future research.